The Effect of Social Media Use on Personality and Student Discipline - Amir, Miftah; Syahlan, Fatra; Nugraha, Derry (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
Along with the development of information technology, the use of the internet in education has also progressed. The use of the internet is no longer limited to distance education, but has penetrated into the conventional education system. E-learning is a learning model presented in digital format through electronic devices. The purpose of implementing e-learning is to expand access to education for the wider community. One of the supporting factors for the modernization of the education subsystem is the presence of Wifi facilities in educational institutions which are expected to increase student learning motivation. As agents of change, students are required to be able to exercise social control over themselves from the adverse effects of freedom to access the internet through these WiFi facilities, so that the education process can run as expected. This study aims to examine the influence of Social Media on personality and student learning discipline. The research sample was students of Linggabuana PGRI University Sukabumi in the academic year 2023/2024. The method used is quantitative descriptive analysis with data collection techniques in the form of questionnaires. The sample amounted to 100 students of Linggabuana PGRI University Sukabumi. The results showed that the effect of using Social Media on personality and discipline was 15.6%. Based on these results, it can be concluded that Social Media affects personality and discipline.